Changes in tribological performance of high molecular weight high density polyethylene induced by the addition of molybdenum disulphide particles - Pettarin, Valeria (2010)
Through this work, the effect of the addition of commercial molybdenum disulphide on the tribological behavior of high molecular weight high density polyethylene was assessed. Determination of several tribological parameters (kinetic coefficient of friction by sliding testing, static coefficient of friction by scratch testing, sliding wear rate by roller-on-plate test, abrasive wear rate by dry sand/rubber wheel test, and surface hardness by microhardness measurements) and microscopical observations (by TOM, SEM and EDAX) were combined in an attempt to elucidate the effect of MoS2 in composites performance. In this way, a complete picture of composites behavior was achieved. An content of MoS2 for minimum wear rate was encountered to be around 10 wt.%. It was found that the solid lubricant increases wear resistance under both sliding and abrasive wear conditions. It seems that depending on wear condition MoS2 acts in a different way. It appears that MoS2 contributes to dissipate the generated heat, thus decreasing wear due to surface melting of the polymer. Under sliding conditions, an adhesive wear mechanism became dominant which is characterized by the formation of a uniform and adherent transfer film on the counterface. Under abrasive conditions a positive rolling effect of MoS2 particles was found. Amounts of filler larger than 10% resulted in a detriment of wear resistance due to weak microstructures which lead to the occurrence of micro-cracking wear mechanism. Besides, the effect of MoS2 particles upon HMW-HDPE stress–strain and fracture behavior was checked for the composite with the best wear performance. Low strain mechanical properties of HMW-HDPE remained almost unaltered while a noticeable change in high strain properties resulted from the introduction of filler. Fracture mode was also changed from stable to unstable under quasi-static conditions and from semi-ductile to brittle under dynamic conditions, with a concomitant abrupt reduction in toughness values.